2018
DOI: 10.3389/fnut.2018.00019
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in the Bin: A Nutritional and Environmental Assessment of Food Wasted in the UK

Abstract: The UK currently has the most detailed, directly measured data for food wasted in the home. This includes information on the exact types of food wasted. These data allow calculation of the nutrients within that waste, as well as its environmental impact. The results progress the conversation beyond how much food is wasted or its energy content; it permits the implications for nutrition and sustainability to be assessed in detail. Data for UK household food waste were expressed as an average waste per capita fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 8 publications
3
32
2
3
Order By: Relevance
“…At the processing plant, there were some established process controls, but these were insufficient to prevent almost 14% or 5-12% of losses observed along the UHT and yogurt production lines, respectively. The nutritional value loss attributed to this was also significant, with both marco-and micro-nutrients disappearing from the food system, in line with previous studies (Cooper et al, 2018;Spiker et al, 2017). As a consequence, the amount of essential nutrients needed for people to meet their Recommended Daily Allowances is lowered, which potentially increases undernutrition.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…At the processing plant, there were some established process controls, but these were insufficient to prevent almost 14% or 5-12% of losses observed along the UHT and yogurt production lines, respectively. The nutritional value loss attributed to this was also significant, with both marco-and micro-nutrients disappearing from the food system, in line with previous studies (Cooper et al, 2018;Spiker et al, 2017). As a consequence, the amount of essential nutrients needed for people to meet their Recommended Daily Allowances is lowered, which potentially increases undernutrition.…”
Section: Discussionsupporting
confidence: 85%
“…Total loss from all products was then summed up and divided with Recommended Daily Allowance (RDA) of adult males and females. The RDA, which represents the daily level of intake that is adequate to meet the nutrient requirements of nearly all healthy people was preferred to other reference values, in line with previous studies (Cooper et al, 2018;Spiker et al, 2017). RDA values were based on the Dietary Reference Intakes guidelines developed by the Food and Nutrition Board and Institute of Medicine (Otten et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study in the United States found that food wasted at the retail and consumption stages on an average day in 2012 contained the recommended daily allowance of dietary fiber for 74 million adult women (Spiker et al 2017). In the United Kingdom, the typical food waste created by one person in one year could provide the nutrients and energy required for six weeks of the year for the average adult woman (Cooper et al 2018). The Global Panel on Agriculture and Food Systems for Nutrition (2018) reports that if rates of food loss and waste increase by around one-third by 2030 (due to rising incomes, urbanization, and failure to take decisive steps to reduce food loss and waste), significant nutrient "disappearance" would occur.…”
Section: Box 23 | Redistribution Of Surplus Food and Food Securitymentioning
confidence: 99%
“…In 2012, the food that was wasted at the retail and consumer levels contained 1,217 kcal, 33 g protein, 5.9 g dietary fiber, 1.7 mg vitamin D, 286 mg calcium, and 880 mg potassium per capita per day according to our estimates. We also estimated what others subsequently termed “nutrient days” (Cooper et al, ) or the number of days of full nutrition that were lost. In subsequent research, we also used the tool to estimate lost nutrition in the vegetables and berries lost on Vermont farms (Neff et al, forthcoming).…”
Section: Proposed Conceptual Frameworkmentioning
confidence: 99%